Long‐term survival of Atlantic salmon following catch and release: Considerations for anglers, scientists and resource managers. (3rd February 2022) - Keefe, Donald; Young, Mark; Van Leeuwen, Travis E.; Adams, Blair
Abstract: To evaluate the scientific basis for catch and release as a management tool, a comprehensive 3‐year study compared long‐term survival of Atlantic salmon that were either angled, radio‐tagged and released, or trapped, radio‐tagged and released (control). Overall, the mean survival probability of angled salmon relative to the control group was between 0.94 and 0.98. At cool to moderate water temperatures (10–18°C) mean survival of angled salmon was between 0.96 and 0.98. Although the number of salmon caught and released above 21°C was low, catchability was slightly reduced at warm water temperatures (21–25°C) and the mean survival probability was between 0.43 and 0.69. Lastly, the number of fish that survived the spawning period did not differ between the angled group and the control group. However, the mean percentage of fish that overwintered and migrated downstream through a counting fence to sea was between 9% and 10% for those that were caught and released and between 13% and 19% for the control group. Results of this study suggest that mortality of caught and released Atlantic salmon can be delayed but remains low at cool to moderate water temperatures.